The Pedagogical Practicum Journey Towards Becoming an English Language Teacher - Edgar Lucero; Katherin Roncancio-Castellanos (Universidad Nacional de Colombia, 2019)
This article discusses English language pre-service teachers' pedagogical practicum experiences. We compiled, from their teacher journals and group talks, the lived teaching experiences of a group of 34 pre-service teachers who were majoring in English language education at a private university in Bogota, Colombia. The analysis of their stories makes us realize that their first practicum experiences are full of feelings and emotions, and that their first teaching practices are based on their mentor teachers' pieces of advice. These first experiences, in turn, develop the foundation upon which they build themselves as English language teachers.